Antioxidant Potential of Adiponectin and Full PPAR-γ Agonist in Correcting Streptozotocin-Induced Vascular Abnormality in Spontaneously Hypertensive Rats - Sheryar Afzal; Munavvar Abdul Sattar; Edward James Johns; Olorunfemi A. Eseyin; Ali Attiq (PPAR Research)
Oxidative stress, which is associated with metabolic and anthropometric perturbations, leads to reactive oxygen species production and decrease in plasma adiponectin concentration. We investigated pharmacodynamically the pathophysiological role and potential implication of exogenously administered adiponectin with full and partial peroxisome proliferator-activated receptor-gamma (PPAR-γ) agonists on modulation of oxidative stress, metabolic dysregulation, and antioxidant potential in streptozotocin-induced spontaneously hypertensive rats (SHR). Group I (WKY) serves as the normotensive control, whereas 42 male SHRs were randomized equally into 7 groups (n=6); group II serves as the SHR control, group III serves as the SHR diabetic control, and groups IV, V, and VI are treated with irbesartan (30 mg/kg), pioglitazone (10 mg/kg), and adiponectin (2.5 μg/kg), whereas groups VII and VIII received cotreatments as irbesartan+adiponectin and pioglitazone+adiponectin, respectively. Diabetes was induced using an intraperitoneal injection of streptozotocin (40 mg/kg). Plasma adiponectin, lipid contents, and arterial stiffness with oxidative stress biomarkers were measured using an in vitro and in vivo analysis. Diabetic SHRs exhibited hyperglycemia, hypertriglyceridemia, hypercholesterolemia, and increased arterial stiffness with reduced plasma adiponectin and antioxidant enzymatic levels (P<0.05). Diabetic SHRs pretreated with pioglitazone and adiponectin separately exerted improvements in antioxidant enzyme activities, abrogated arterial stiffness, and offset the increased production of reactive oxygen species and dyslipidemic effects of STZ, whereas the blood pressure values were significantly reduced in the irbesartan-treated groups (all P<0.05). The combined treatment of exogenously administered adiponectin with full PPAR-γ agonist augmented the improvement in lipid contents and adiponectin concentration and restored arterial stiffness with antioxidant potential effects, indicating the degree of synergism between adiponectin and full PPAR-γ agonists (pioglitazone).